MEDIATION IN MARRIAGE ANNULMENT CASES UNDER SUPREME COURT REGULATION (PERMA) NO. 1 OF 2016 ON COURT MEDIATION PROCEDURES - Burhanuddin, Ahmad; Marnila Sari, Nani; Sahrin, Muhammad Farhan (El-Izdiwaj: Indonesian Journal of Civil and Islamic Family Law, 2025)
The Religious Court of Tanjung Karang, in Decision Number 1240/Pdt.G/2024/PA.Tnk, conducted mediation in a marriage annulment case. Although Article 4 paragraph (2) letter d of Supreme Court Regulation (PERMA) Number 1 of 2016 stipulates that marriage annulment cases are exempted from mandatory mediation, the judge exercised discretion to carry out mediation in this case.This research employs normative and empirical juridical methods with a case study approach. The findings indicate that the implementation of mediation in marriage annulment cases does not contravene procedural law, as the exemption in PERMA Number 1 of 2016 does not amount to an absolute prohibition. On the contrary, mediation in this context provides the parties with an opportunity to resolve their disputes amicably and in a familial spirit, reflecting the values of deliberation in Islamic law as well as the modern judicial principles of being swift, simple, and low-cost. Therefore, the judge’s decision is considered lawful and in accordance with the prevailing legal framework.